Praktik Jual Beli Barter Sparepart Sepeda Motor Di Kelurahan Sadabuan Kota Padangsidimpuan Ditinjau Dari Kompilasi Hukum Ekonomi Syariah - Husein, Rahmat; Ahmatnijar, Ahmatnijar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The background of the problem in this research is the sale and purchase of spare parts motorcycles that are still in the credit period, but the debtor has default against one of the leasing companies in the city of Padangsidimpuan. As a result of the default, the leasing party will withdraw the motorcycle before the leasing party comes to recall the motorbike In this case, the debtor has sold some of the motorcycle spare parts with barter trading system. For example, such as rear shock (spring), tires and others. Whereas in the Compilation of Sharia Economic Law Article 266 which states: contains about Tenants are prohibited from renting and lending ijarah objects to other parties except with the permission of the party who rents out The formulation of the problem in this study is how to practice buying and selling motorcycle spare parts barter and a review of the Sharia Economic Law Compilation on the sale and purchase of motorcycle spare parts barter in the Sadabuan urban village Padangsidimpuan The method used in this research is the research method qualitative. As for the data collection techniques in the form of interviews and documentation. In this method, the data analysis used is descriptive that is, the researcher analyzes a systematic picture of what is happening in the field. Then perform an analysis of the findings by using adjust between findings and theory From the results that the practice of trading spare parts barter carried out in Sadabuan Village and the community have not fully complied with the requirements regarding buying and selling by barter which is contained in several provisions and can be eliminating the benefits, so the sale and purchase of spare parts is not in accordance with Compilation of Sharia Economic Law and because of the lack of clarity with objects or goods on the object being traded.